Risiko Produksi dan Faktor-faktor yang Memengaruhi Pendapatan Usahatani Kopi Robusta di Desa Gombengsari Kecamatan Kalipuro Kabupaten Banyuwangi - Shafira, Alivia Nur; Aji, Joni Murti Mulyo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The robusta coffee plantation sector in Gombengsari Village has the potential to become a leading sector worth developing. However, the production of robusta coffee in Gombengsari has not been carried out optimally. This indicates the presence of problems that can pose production risks in robusta coffee farming. The purpose of this study is to determine the level and strategy of production risk management, as well as to identify the factors that influence the income of robusta coffee farming in Gombengsari Village, Kalipuro District, Banyuwangi Regency. The methods used by researchers are descriptive and analytical methods. The data analysis methods used are the Coefficient of Variation (CV) analysis, descriptive analysis with a quantitative approach based on Malton's theory, and multiple linear regression analysis. The results of the analysis show that 1) The Coefficient of Variation (CV) obtained is 0.79, indicating that the level of production risk for robusta coffee experienced by farmers in Gombengsari village is high. 2) The risk management strategies employed by robusta coffee farmers in Gombengsari village include ex-ante, interactive, and ex-post management strategies. 3) The calculated F value (1247.096) ≥ F table (2.29) and the significance value of the F test in Anova ˃ 0.05 indicate that all independent variables simultaneously influence the income variable of robusta coffee farming.